Pengaruh Literasi Keuangan Terhadap Kebeberhasilan Berwirausaha Dimediasi Self Efficacy pada Gen Z Penerima Kredit Usaha Rakyat di Bank Jambi Cabang Tebo (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of financial literacy on entrepreneurial success with self-efficacy as a mediating variable in Generation Z recipients of People's Business Credit (KUR) at Bank Jambi Tebo Branch. The study used a quantitative approach with a survey method. The sampling technique was carried out by purposive sampling with a total of 95 respondents from Generation Z KUR recipients from January 2025 to November 2025. Data were collected through a questionnaire using a Likert scale and analyzed using Partial Least Squares (PLS). The measurement model was used to test the validity and reliability of the instrument, while the structural model was used to examine the causal relationship between variables and test the hypothesis. The results showed that financial literacy had a positive but insignificant effect on self-efficacy. Self-efficacy was proven to have a positive and significant effect on entrepreneurial success. In addition, financial literacy did not have a direct effect on entrepreneurial success. However, the results of the indirect effect test showed that financial literacy had a significant effect on entrepreneurial success through self-efficacy. These findings indicate that self-efficacy plays a significant role as a mediator between the influence of financial literacy on entrepreneurial success among Generation Z KUR recipients. This research provides an empirical contribution to understanding the role of psychological factors in enhancing the success of young entrepreneurs based on financial literacy.